Promoting regional trade to enhance food security: a case study on the border region of Tanzania and Zambia - Bese, D.; Düchting, A.; Gebauer, H.; Gerken, A.; Maeda, C.; Manyong, Victor M.; Rupschus, C.; Starosta, S. (2009)
Food security is an issue of high importance for Sub-Saharan African countries. With the on-going process of regional integration, the promotion of regional trade between neighbouring countries is one strategy to enhance food security.The study introduces an Analytical Framework (AF) to evaluate the potentials of regional trade to enhance food security. Three working levels are defined: (1) A desk study to identify relevant countries or regions, (2) a fact-finding mission to collect in-depth data and (3) an assessment to evaluate the potentials.The AF is implemented in a case study on crossborder trade between Tanzania and Zambia. Both countries are members of the Southern African Development Community and are intensifying co-operation and trade liberalisation. Although being generally food secure, Tanzania still faces food shortages. The Government pursues an interventionist policy by purchasing food in surplus areas to sell these at subsidised prices in deficit regions. This is combined with several barriers for crossborder trade, e.g. an export ban on food staples. Zambia's food security policies are biased towards maize as major food staple. The Government intervenes on domestic markets and provides farmers with subsidised inputs. Zambia's Northern Province is generally food secure but Zambia sometimes faces food shortages. The Mbeya and Rukwa Regions in Tanzania have favourable natural conditions. The productivity of the agricultural sector is above national level and the area produces surpluses.Import quantities to Zambia are influenced by the imposed export ban. Besides formal trade, the importance of informal cross-border trade with maize has increased. Trade is ampered by a number of non-tariff barriers, ranging from cost-intensive and time-consuming customs procedures to road blocks. Most of the non-tariff barriers are relevant for formal and informal trade. The assessment of the policy measures shows conflicts of interests between national food security on one side and agricultural trade liberalisation on the other side. Market interventions have negative effects on trade in general. Additionally, the Tanzanian export ban creates disincentives for farmers and traders. The assessment shows potentials for increasing the crossborder trade between both countries. The recommendations concentrate on the potentials to expand their involvement in trade.